MONEY AND REAL ECONOMY RELATIONSHIP: THE CASE OF SAUDI ARABIA - Masudul Alam Choudhury (Universitas Trisakti, 2013)
The money-economy relationships for Saudi Arabia are theoretically conceptualized and empirically estimated to derive the nature of such relationships in the perspectives of economic stabilization and sustainable development of Saudi economy. The M1 supply of money is found to be the predominant component of money supply in Saudi Arabia contributing to real sectoral linkage between money and development. Yet changes in other components of money supply, M2 and M3, are found to indicate a growing trend towards a regime of long-run savings as opposed to spending in the Saudi Economy. Policy recommendations are derived. The statistically significant relationship of M1 supply of money in Saudi Arabia indicates the prominent role of money in circulation in the real economy. This is a strong feature of endogenous money. Endogenous money is referred to here as the resource mobilization of money into real economic activities. Money therefore established a systemic general equilibrium relationship with other real sector variables.